2010
DOI: 10.1111/j.1600-9657.2009.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors associated with traumatic dental injuries in preschool children: a Poisson regression analysis

Abstract: These findings indicate the need for preventive orientation regarding TDI, in order to educate parents and caregivers about supervising infants, particularly those with increased overjet and whose mothers have a higher level of education. Poisson regression with robust variance represents a better alternative than logistic regression to estimate the risk of dental trauma in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
75
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(95 citation statements)
references
References 27 publications
9
75
1
10
Order By: Relevance
“…7 A mother's schooling exerted no influence on the occurrence of TDI. This finding is in agreement with data described in previous studies, 1,5,11,12 but differs from findings described in cross-sectional and longitudinal investigations carried out on Brazilian children, in which TDI was associated with a higher level of a mother's schooling in some studies, 14,15 and a lower level of a mother's schooling in others. 7 These differences may be attributed to how this variable is categorized.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…7 A mother's schooling exerted no influence on the occurrence of TDI. This finding is in agreement with data described in previous studies, 1,5,11,12 but differs from findings described in cross-sectional and longitudinal investigations carried out on Brazilian children, in which TDI was associated with a higher level of a mother's schooling in some studies, 14,15 and a lower level of a mother's schooling in others. 7 These differences may be attributed to how this variable is categorized.…”
Section: Discussionsupporting
confidence: 90%
“…However, other studies have found no association between TDI and monthly household income, as confirmed in multivariate analyses. 11,12,14,15,16 Multivariate analysis allows evaluating interactions among variables, which is an important aspect when studying conditions with multifactor etiology, such as TDI. Comparisons among studies must be done cautiously because of methodological differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations